Effects of preservation period on quality of chilled semen of Boer-cross bucks - Amin, MA; Saha, A; Bhattacharjee , J; Juyena, NS; Bhuiyan, MMU (Bangladesh Veterinarian, 2023)
Characteristics of fresh semen and the effect of chilling on the quality of semen of Boer-cross bucks were studied. Fresh semen from two Boer-cross bucks was evaluated for volume, mass motility, progressive motility, viability, concentration and proportion of spermatozoa with normal acrosome, mid-piece and tail. The semen was diluted at 1:4 ratios with Tris-fructose-citrate-egg yolk extender, preserved at 4ºC for 72 hours and evaluated for progressive motility and proportion of spermatozoa with normal acrosome, mid-piece and tail at 24-hour intervals for three days. The mean volume, mass motility, progressive motility, sperm viability, sperm concentration and proportion of spermatozoa with normal acrosome, mid-piece and tail of fresh semen of Buck 1 and Buck 2 were 370.0 ± 0.1 and 410.0 ± 0.1 μl, 3.3 ± 0.4 and 3.4 ± 0.1, 74.0 ± 13.9 and 76.0 ± 6.5%, 82.3 ± 7.5 and 84.3 ± 4.2%, 2730.0 ± 740.9 × 106/ml and 2584.0 ± 470.1 × 106/ml, and 93.3 ± 2.9 and 94.9 ± 0.4%, respectively. The progressive motility in chilled semen of Buck 1 at days 1, 2 and 3 was 61.2 ± 7.3, 51.0 ± 7.3 and 39.0 ± 5.5%, respectively; in Buck 2, it was 60.6 ± 6.8, 50.2 ± 6.2 and 39.2 ± 5.4%, respectively. The difference in semen parameters among days of preservation was significant (P<0.05) in both bucks. The proportion of spermatozoa with normal acrosome, mid-piece and tail in chilled semen of Buck 1 at days 1, 2 and 3 was 88.0 ± 7.0, 88.8 ± 5.9 and 87.1 ± 7.7%, respectively; in Buck 2, it was 86.6 ± 4.8, 84.1 ± 4.6 and 81.8 ± 4.9%, respectively. It is suggested that the characteristics of fresh semen of these two Boer-cross bucks were within normal range. The quality of semen of Boer-cross bucks deteriorated with chilling up to 72 hours. Improvement of the preservation protocol is required to obtain satisfactory quality of chilled semen of Boer-cross bucks. Bangl. vet. 2022. Vol. 39, No. 1-2, 34–42